Experimental Investigations on Computer-Based Methods for Determination of Static Electromagnetic Characteristics of Switched Reluctance Motors - Gobbi, R.; Sahoo, N.C.; Vejian, R. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
Because of the doubly salient structure of the switched reluctance motor (SRM) and its intentional operation in deep magnetic saturation for higher power density, its static electromagnetic characteristics are highly nonlinear functions of rotor position and phase current. This makes the accurate experimental measurement/determination of these characteristics a difficult task. This paper presents a comprehensive discussion and analysis on the different (most practiced) computer-based methods for the determination of these characteristics for a typical SRM. A digital signal processor (DSP)-based completely automated SRM drive system has been used for these studies. For all the offline computations, user-friendly MATLAB/Simulink-based models have been developed. The experimental methods, computational models, measurement results, and appropriate postmortem discussions for the determination of static flux linkage, inductance, and electromagnetic torque characteristics for an 8/6 four-phase SRM are reported.